Halal Tourism Compliance Analysis at Culinary Agritourism Destinations: A Qualitative Case Study of Sari Kedele Farm, Sumedang Regency, West Java, Indonesia - Attaluni, Haidar Barok (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2024)
Indonesia achieved the top-ranked position in the 2023 Global Muslim Travel Index (GMTI), yet empirical research examining how individual culinary agritourism destinations comply with halal tourism standards remains limited. This study analyses the halal tourism compliance of Sari Kedele Farm (SKF), a culinary agritourism destination in Sumedang Regency, West Java, against the normative framework established by the GMTI, the DSN-MUI Fatwa No. 108/2016 on Halal Tourism, and the Tim Percepatan Pengembangan Pariwisata Halal (TP3H) criteria. A qualitative single-case study design was employed, with primary data drawn from semi-structured interviews with the founder-owner and the operational manager, supplemented by non-participant observation across seven site visits and document analysis of company records, menus, and promotional materials. Data were analysed using thematic analysis with a deductive framework derived from three compliance dimensions: destination facilities and environment, food and beverage halal assurance, and management and human-resource governance. The findings reveal that SKF demonstrates substantial compliance across most halal tourism criteria: the destination offers a family-friendly environment with adequate prayer facilities, serves exclusively halal-certified food with transparent supply-chain sourcing, employs hijab-wearing female staff, prohibits alcohol and non-halal entertainment, operates a riba-free cash-and-digital payment system, and attracts a predominantly Muslim visitor base. However, three compliance gaps are identified: the absence of formal halal certification from BPJPH/MUI for the on-site restaurant, the lack of gender-segregated recreational facilities, and the use of a conventional rather than Sharia-explicit management framework. The study contributes to the halal tourism literature by providing destination-level compliance evidence from a non-traditional tourism setting—culinary agritourism—and proposes a nine-element operational reform pathway for transitioning from de facto to certified halal tourism compliance. Practical implications for destination managers, local government tourism offices, and the national halal tourism acceleration programme are discussed